Strategies For Strengthening New Student Communication In The Campus Environment Through Assertive Communication Training - Mira Wahyu Kusumawati; Elok Faradisa; Sigit Yulianto; Amin Aji Budiman; Ajeng Salwa Salsabila (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2025)
Background: New students frequently encounter communication challenges as they adjust to the campus environment, which can affect their learning process and social interactions. Assertive communication training is one effective strategy to enhance students’ communication skills. This study aims to analyze the effectiveness of assertive communication training in improving the communication skills of new students within the campus setting. Methods: The study was conducted by providing an assertive communication orientation to 175 nursing students. Data were collected using pretest and posttest assessments to measure changes in students’ knowledge of assertive communication. Results: The pretest results showed that 35 students (25%) had low knowledge, and only 15 students (8.5%) demonstrated high knowledge of assertive communication. After the training, none of the students remained in the low knowledge category; 88 students (50.3%) had high knowledge, and 87 students (49.7%) had moderate knowledge. Conclusion: Assertive communication training is effective in enhancing the knowledge and communication skills of new students. These findings can serve as a basis for developing soft skills training programs to support students’ adaptation to the higher education environment.